Temporal dynamics of Candida albicans morphogenesis and gene expression reveals distinctions between in vitro and in vivo filamentation - Rohan S. Wakade; Melanie Wellington; Damian J. Krysan (mSphere, 2024)
ABSTRACTCandida albicans is a common human fungal pathogen that is also a commensal of the oral cavity and gastrointestinal tract. C. albicans pathogenesis is linked to its transition from budding yeast to filamentous morphologies including hyphae and pseudohyphae. The centrality of this virulence trait to C. albicans pathobiology has resulted in extensive characterization of a wide range of factors associated with filamentation with a strong focus on transcriptional regulation. The vast majority of these experiments have used in vitro conditions to induce the yeast-to-filament transition. Taking advantage of in vivo approaches to quantitatively characterize both morphology and gene expression during filamentation during mammalian infection, we have investigated the dynamics of these two aspects of filamentation in vivo and compared them to in vitro filament induction with “host-like” tissue culture media supplemented with serum at mammalian body temperature. Although filamentation shares many common features in the two conditions, we have found two significant differences. First, alternative carbon metabolism genes are expressed early during in vitro filamentation and late in vivo, suggesting significant differences in glucose availability. Second, C. albicans begins a hyphae-to-yeast transition after 4-h incubation while we find little evidence of hyphae-to-yeast transition in vivo up to 24 h post-infection. We show that the low rate of in vivo hyphae-to-yeast transition is likely due to the very low expression of PES1, a key driver of lateral yeast in vitro and that heterologous expression of PES1 is sufficient to trigger lateral yeast formation in vivo.IMPORTANCECandida albicans filamentation is correlated with virulence and is an intensively studied aspect of C. albicans biology. The vast majority of studies on C. albicans filamentation are based on in vitro induction of hyphae and pseudohyphae. Here we used an in vivo filamentation assay and in vivo expression profiling to compare the tempo of morphogenesis and gene expression between in vitro and in vivo filamentation. Although the hyphal gene expression profile is induced rapidly in both conditions, it remains stably expressed over a 12-h time course in vivo while it peaks after 4 h in vitro and is reduced. This reduced hyphal gene expression in vitro correlates with reduced hyphae and increased hyphae-to-yeast transition. By contrast, there is little evidence of hyphae-to-yeast transition in vivo.